If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 4 + 2x) = 63 Reorder the terms: 7(4 + 3x + 2x) = 63 Combine like terms: 3x + 2x = 5x 7(4 + 5x) = 63 (4 * 7 + 5x * 7) = 63 (28 + 35x) = 63 Solving 28 + 35x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 35x = 63 + -28 Combine like terms: 28 + -28 = 0 0 + 35x = 63 + -28 35x = 63 + -28 Combine like terms: 63 + -28 = 35 35x = 35 Divide each side by '35'. x = 1 Simplifying x = 1
| 0.80x+20.00=281.60 | | y=-9/7x+2 | | x+14=29 | | 0=-100+(.7q-6)q | | 2(22-3*7)= | | 28-16=3(x-1) | | b+a=cx | | 2(x+6)=12+2x | | ln(2x^4+10x^3)+ln(1/(3x^3)) | | 7-6=12-2x | | 0=cx-a+b | | cx-a+b=2b | | 5x+-10=21-6x | | 9+x/2=10 | | 1x-4y=-27 | | y=5sinx+3x | | -4x/3=12 | | 355-5x=0+5x | | -3/4y+2=14 | | -2(3n-1)-n=5(n-4) | | 6/5+x=4/7 | | 120+10x=15+4x | | 2x+(2*2*x+5)=949 | | x-52=194 | | 5*5x=8*5 | | 6x-28=x-8 | | 3x+(2*2*x+5)=949 | | 10n+15=54n+48+4 | | 3[2x-9]-10=-17 | | 2(7-3r)=3r-22 | | (4/(x-5))+(3/(x+4)) | | 14x^2-6x^3=0 |